The Role of Fintech in the Transformation of the Cashless Society of the Sharia Financial Sector with A Literature Review Approach - Wiyani, Sri; Muhammad Syahbudi; Aqwa Naser Daulay (Institut Agama Islam Negeri Parepare, 2025)
The development of financial technology (fintech) has driven a significant transformation in the Islamic finance sector, particularly toward a cashless society, where transactions are conducted without cash. This study aims to analyze the role of fintech in this transformation through a literature review and bibliometric analysis using data from 21 Scopus journals, 26 from Google Scholar, and 15 from Crossref. Of the 62 journals analyzed, approximately 70% indicate that fintech plays a significant role in increasing financial inclusion, operational efficiency, and the development of Sharia-compliant financial products. Innovations such as digital payments, peer-to-peer lending, and Sharia-compliant investments are key drivers of this transition. Analysis using Vosviewer also reveals the dominance of the keyword